Magnetic nanoparticles for radar absorber application : silica coated cobalt-iron nanoparticles and silica coated iron nanoparticles - Leong, Glenn Jie Wei (2016)
Research into Radar Absorbing Materials (RAM) has increased exponentially over the last decade. One main reason is due to the proliferation of the use of stealth technology in armed forces globally. RAM coatings have been found to be an efficient way of reducing Radar Cross Section (RCS) by converting incident radar waves into alternative forms of energy. However, there have been limited studies done thus far on nano-scale RAM and its radar wave capabilities. Hence, this report aims to fill the gap by providing analysis on how Silica coated Cobalt-Iron Nanoparticles (CoFe2@SiO2) and Silica Coated Iron Nanoparticles (Fe@SiO2), which can be used as RAM, are able to improve and enhance present day high performance radar wave attenuation technology. This will also provide the opportunity whereby a direct comparison of the radar wave attenuation capability can be made between both CoFe2@SiO2 and Fe@SiO2 nanoparticles. The nanoparticles were characterized by XRD, TEM, FTIR and VNA. Results obtained have concurred with the available literatures. Thus, though both CoFe2@SiO2 and Fe@SiO2 nanoparticles have the potential to be excellent RAM, however greater promise lies with the use of CoFe2@SiO2 as a RAM.